A tradição discursiva carta pessoal: um olhar sobre o livro didático de língua portuguesa do ensino médio - Nunes , Cícero Barboza (2015)
This study, carried out through the Postgraduate Program in Linguistics and Education of the Universidade Federal da Paraíba, aims to analyze the presence of the discursive tradition in personal letters in the textbooks of Portuguese Language of High School. We start from this study of the concept of Discursive Tradition (TD) defined by Kabatek (2005) that is the repetition of a text, a textual form or a particular way of writing or speaking that acquires the value of a proper sign , Meaningful). Thus, in evidencing that the texts have a history and that this textual history - considered from its relation of tradition and updating - directly influences the textual uses, independently of its modes of enunciation. And because we consider the personal letter a rich TD genre to explore aspects that pervade the linguistic, especially since it results from social interaction, this study becomes relevant for investigating the permanence or not of such gender in the teaching of Portuguese in high school . Considering the propaedeutic nature of Portuguese language teaching (hereinafter LP), we attribute to this discipline the development of studies and reflection on the different language practices, namely: reading, listening, producing texts (oral and written), Reflection and linguistic analysis. This discipline, as part of the Brazilian school curriculum, adds a great responsibility in the cognitive development. In order to do this, we must consider language as an instrument that goes beyond the notion of expression of national identity, being considered, at the same time, as an instrument that seeks to establish social relationships, order reality data, understand non-verbal languages, Writing, organizing and recording acquired knowledge, etc. With this, it is necessary to think that the personal letter, like all discursive genres, has its production from the social dimension and that its insertion in the Portuguese language classes can contribute to the cultural enrichment of the student. The results of this study show traces of changes in the work with the personal letter genre in High School in the last decades, which can be directly related to the restructuring that Portuguese language teaching has undergone in recent years. These results become relevant to reflect proposals of didactic activities that consider the genre personal letter useful to explore possibilities to develop the reflection of the student about the gender in its linguistic, historical and social aspects. In this way, we take as a background the theoretical assumptions of Coseriu (1979), Koch (1997), Oesterreich (1997), Kabatek (2003, 2005 and 2006), Patriota (2010), Longhin (2014), Bakhtin , Marcuschi (2001), Bronckart (2006), among others.